Respuesta :

Answer:

-7/5 if your function really is f(x)=-5x-7

Step-by-step explanation:

The zeros of an expression are the numbers you can plug into that expression that will make that expression 0.

So what value of x will make the expression

-5x-7=0.

You don't have to this by observation. We can just solve it and see.

-5x-7=0

Add 7 on both sides:

-5x. =7

Divide both sides by -5:

x. =7/-5

x. =-7/5

So -7/5 will make the expression equal to 0.

Let's test this:

-5x-7 when x=-7/5

-5(-7/5)-7

7-7

0

So it does indeed.